Relationship between resting heart rate and anthropometric, metabolic and hemodynamic parameters in the elderly aged 80 years and over - Fabrício E. Rossi; Ana Laura Ricci-Vitor; Igor C. Gomes; Vanessa R. Santos; João Paulo J. Sabino; Luiz Guilherme S. Branco; Diego G. D. Christofaro; Luiz Carlos M. Vanderlei; Ismael F. Freitas Junior (Universidade Estadual Paulista (UNESP), 2016)
Abstract This study examined the relationship between resting heart rate (RHRr) and anthropometric, metabolic and hemodynamic parameters in subjects aged 80 years and over. One hundred thirteen individuals were divided into two groups (RHR:<66 beats/min and ≥66 beats/min). Anthropometric parameters (weight, height, body mass index and waist circumference (WC) were measured. Hemodynamic parameters (systolic (SBP) and diastolic (DBP) pressure) were measured and pulse pressures (PP) were obtained. Metabolic parameters were fasting blood glucose, triglycerides and total cholesterol. In elderly aged 80 and over, RHR influenced the changes observed in DBP, PP and triglycerides. Additionally, subjects with RHR≥66 beats/min had higher DBP, glucose, total cholesterol and lower PP as compared with elderly with RHR<66 beats/min. Men demonstrated greater weight, height, and WC than women while women had higher percentage of body fat, trunk fat, and higher total cholesterol. Thus, subjects with 80 years old and over who present RHR≥66 have higher DBP and lower PP and heart rate variability compared with the elderly with RHR<66.